Current and emerging investigational venetoclax-based therapies in chronic lymphocytic leukemia. (3rd June 2021) - Molica, Stefano; Allsup, David; Gianfelici, Valentina; Levato, Luciano; Aiello, Vincenzo; Bailey, James; Polliack, Aaron
ABSTRACT: Introduction : Venetoclax has emerged as a breakthrough treatment which has revolutionized the therapeutic paradigm of chronic lymphocytic leukemia (CLL). This is primarily attributed to the efficacy of venetoclax as a time-limited, chemo-free, therapy in a field dominated by targeted agents given on a continuous schedule. Furthermore, compelling clinical data support the use of venetoclax in combination with other targeted agents in the hope of preventing drug resistance due to the emergence of acquired mutations. Areas covered : This paper provides an overview of clinical results of newly approved or investigational venetoclax-based therapies for CLL. In view of current and potential roles in CLL care, the strengths and disadvantages of venetoclax-combinations are discussed. The MEDLINE database, ClinicalTrials.gov and conference proceedings were all reviewed to select the relevant literature. Expert opinion : While the advent of venetoclax-based combinations has significantly expanded the therapeutic options for patients with CLL, further research with longer follow-up is required to address remaining open questions such as (I) the role of venetoclax as fixed duration therapy(II) timing and threshold of minimal residual disease (MRD) assessment for therapy discontinuation, (III) the efficacy of novel triplet combinations with venetoclax as backbone therapy, (IV) indications for the re-initiation of therapy with venetoclax.